THE ENVIRONMENTAL VALUE IN SNYDER’S MOTHER EARTH: WHALES - Iftinan Rose Putri Safana (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Protecting nature is important to prevent disasters. It is necessary to shape the environmental values in a person to encourage nature preservation to have positive attitudes and behavior toward nature. The positive attitudes and behavior toward nature can be expressed through literature in poetry. Snyder's Mother Earth: Whales is a poem that promotes environmental values. Therefore, this study aimed to investigate how literary devices reveal environmental values in Snyder's Mother Earth: Whales. This study used an Ecocriticim approach and environmental values concept by Stern and Dietz to analyze on of Gary Snyder's poems in Turtle Island anthology of poems entitled Mother Earth: Whales. This study found that, inÂ Mother Earth: Whales, Snyder endeavored to reveal environmental value of biospheric value by using figurative languages. In this poem, he used seven cynicisms, three similes, two allusions, two personifications and four metaphors. Furthermore, the researcher suggests a future researcher to use pragmatic approach and VBN theory.